Factors affecting intention to continue volunteering with job satisfaction as mediation - Deasy Aseanty; Andreas Wahyu Gunawan; Giane Julieta (Business and Entrepreneurial Review, 2022)
This study discussed whether there is a positive influence between Volunteer Management and Work Environment on Intention To Continue Volunteering mediated by Job Satisfaction of Central Jakarta Disaster Siaga Taruna (TAGANA) volunteers. This study aims to analyze the variables namely Volunteer Management, Work Environment, Intention To Continue Volunteering and Job Satisfaction and aims to analyze the positive influence between Volunteer Management on Job Satisfaction, To analyze the positive influence between Work Environment on Job Satisfaction, To perform analysis of the positive influence between Job Satisfaction on Intention To Continue Volunteering, To analyze the positive influence between Volunteer Management on Intention To Continue Volunteering mediated by Job Satisfaction, To analyze the positive influence between Work Environment on Intention To Continue Volunteering. The research method is descriptive quantitative with the aim of testing hypotheses, the data used are cross sectional, the unit of analysis used is the individual and the background of this research is no contrived setting. This research is related to the field of Human Resource Management, in particular to see the relationship between the Job Satisfaction variable with the concept of Green Society and Green Human Resource Management. The results of this study indicate that the Volunteer Management and Work Environment variables have a positive effect on Job Satisfaction, the Job Satisfaction variable has a positive effect on Intention To Continue Volunteering, Volunteer Management and Work Environment have a positive effect on Intention To Continue Volunteering mediated by Job Satisfaction. The limitations of this research are that it is only conducted in one organization, namely Central Jakarta Disaster Preparedness Youth (TAGANA), the research variables used are only Volunteer Management, Work Environment, Intention To Continue Volunteering and Job Satisfaction and the research respondents are volunteers in the Disaster Preparedness Team. (TAGANA) Central Jakarta.